PENGARUH SUHU DAN WAKTU SEDUH TERHADAP KADAR KLORIN TEH CELUP DI POLTEKKES KEMENKES BENGKULU TAHUN 2011 - Halimah, Halimah (JURNAL MEDIA KESEHATAN, 2012)
The tea bag is packed with a tea bag made ​​of special paper and given a thread. Many Peoples are still do not know that the paper used to wrap tea contains chlorine. Chlorine is a substance used in the paper industry serves as a bleach and disinfectant. unconsciously, the longer brewing of tea cause the chlorine contained in the paper tea bags will also be dissolved. This study aims to determine the temperature and the effective time for brewing the tea bag so that the chlorine content of tea steeping water at low concentrations. This type of research is a quasi experimental laboratory. The study population was all the tea bags, measuring 2 grams. The number of samples used 27 tea bags, divided into 9 treatments and 3 replications. The results of statistical tests indicate there is a difference levels of chlorine between the temperature variation and brewed time. LSD test at 5% there are differences in average levels of chlorine in the treatment of A1B1 and A1B2 to A1B3, A2B1 and A2B3 and A3B1 a2b2 on and A3B2 to A3B3. Low levels of chlorine in the treatment of A1B1 Yaitu suhu 60 c dalam waktu 3 menit (0004 ppm) and the highest levels of chlorine in the treatment of A3B3 Yaitu suhu 100 C dalam waktu 7 menit (0013 ppm).